EFFICIENCY FERTILIZING IN THE TECHNOLOGY OF RED CABBAGE GROWING - Михайлин, В. І. (Scientific Progress & Innovations, 2014)
Localization of fertilizing and strengthen optimization of mineral nutrition through the use of micronutrients, providing increased yields when grown red cabbage on irrigated black soils on the left- Forest-steppe of Ukraine. The greatest economic effect provides locally application N45P45K30 with foliar feeding by complex fertilizer "Nutrivant plus oil" that gives further 5,92 thousand uah/ha, profitability –- 87% coefficient of bioenergetic efficiency – 2,51.